Shakespeare for Children: Macbeth - Joseph, Mary (CSS Bookshops Ltd, 2006)
This series written in Simple english but still retaining a great deal of the flavour of shakespeare's own words, will hopefully induce children to find out more and more about the works of this great playwright.
Keywords: Tales / Legend - Shakespeare